Magnetic resonance imaging findings of a patient with bilateral submandibular gland aplasia - Alkan, Ender; Kara, Turgay; Öztürk İnal, Zeynep (The European Research Journal, 2018)
Aplasia of the major salivary glands are very rare, and commonly occurs at the parotid gland. Patients are usually asymptomatic and diagnosed incidentally. But dry mouth, difficulty in swallowing, dental problems may be seen. Also mass complaints may occur due to compensatory hypertrophy of the other major salivary glands. Herein, we presented the magnetic resonance imaging findings of a very rare case of bilateral submandibular gland aplasia with compensatory hypertrophy of sublingual glands.